Clinical utility of TIRADS and ultrasound elastography in characterization of thyroid nodules - Sachdev, Namrita; ., Sana; Gupta, Shivani; Prasad, Akhila (International Journal of Research in Medical Sciences, 2019)
Background: Thyroid nodules are a common entity in an iodine deficient population, however malignant nodules are relatively uncommon with excellent prognosis. Ultrasound elastography is a useful tool for characterization of nodules and allows selection of tumors for FNAC. This study aimed to evaluate the diagnostic value of strain elastography and acoustic radiation force impulse (ARFI) imaging in differentiating malignant from benign thyroid nodules. Methods: This study included 100 thyroid nodules evaluated using ultrasound TIRADS classification. Strain elastography evaluated the nodules using the elasticity score and strain ratio followed by VTI and shear wave velocity generated from ARFI data to characterize the nodules. Final diagnoses were obtained from cytological and/or histological evaluation. The diagnostic performance of the two elastography methods was analyzed and compared by multiple receiver operating characteristic curve analysis. Results: Of the 100 thyroid nodules observed in 100 patients (82 females and 18 males), 22% were malignant nodules and 78% were benign. The cut off values for elasticity scores, mean SR, VTI grade and mean SWV for predicting malignant thyroid nodules were greater than or equal to score 2, 2.4, grade 3, 2.5m/s respectively. The area under the receiver operating characteristic curve for elasticity score, mean SR, VTI grade and mean SWV was 0.79, 0.78, 0.89 and 0.84, respectively (P>0.05) and the accuracy was 74, 81.6, 88 and 87.5%, respectively (P>0.05). The accuracy of the combined use of conventional sonography, strain elastography and ARFI imaging was 85.6% respectively, which was higher than that of conventional sonography (P>0.05). Conclusions: Strain elastography and ARFI imaging have high sensitivity and specificity for differentiating malignant from benign thyroid nodules and therefore have good clinical utility in evaluating these lesions.